Preparation and characterization of high-K dieletric material of CCTO by using microwave processing technique. - Hutagalung, Sabar Derita (Universiti Sains Malaysia, 2008)

(untitled)
In this project, three different methods had been applied to synthesize high-k dielectric materials of CaCu3Ti40 12 (CCTO).